Fabrication and characterization of perovskite ferroelectric PMN/PT ceramic nanocomposites - Wongmaneerung R. (2014)
The potential of a ceramic nanocomposite technique employing a simple bimodal particle size packing and a pressureless sintering process as a low-cost and simple ceramic processing to obtain perovskite ferroelectric ceramics in the PMN/PT system was demonstrated. Attention was focused on relationships between chemical composition, densification, microstructure, and electrical properties. It has been found that the phase formation, microstructures, and dielectric properties of ceramic nanocomposites are totally different from those of typical solid solutions. © 2009 Springer Science+Business Media, LLC.